Occupational exposure to non-artificial UV-light and non-melanocytic skin cancer: a systematic review concerning a new occupational disease - Schmitt, Jochen Maximilian; Diepgen, Thomas L.; Bauer, Andrea (Journal der Deutschen Dermatologischen Gesellschaft, 2010)
Although UV exposure is the most important risk factor for cutaneous squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), a systematic review analyzing the risk of occupational UV exposure is missing.
Gesehen am 14.06.2023